The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.32607/20758251-2012-4-2-74-79
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the TGFB1 Gene to Myocardial Infarction Susceptibility

Abstract: Carriage frequencies of alleles and genotypes of theTGFB1 gene polymorphous loci –509C>T (rs1800469), 869T>C (rs1982073), 915G>C (rs1800471), which affect the level of cytokine TGF-β1 production, were analyzed in the patients of Russian ethnic descent with myocardial infarction (MI) (406 cases) and in the control group of the same ethnic descent (198 controls). Significant association with MI was observed in carriage frequencies of the alleleTGFB1*–509T (p=0.046, OR =1.45, 95% CI: 1.02-2.06), genotypes TGFB1*8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
(20 reference statements)
1
8
0
2
Order By: Relevance
“…This is compelling evidence of validity of these associations, at least for the Russian population. It should be mentioned that earlier we described MI-associated genetic variants TGFB1 rs1982073 [ 24 ] and CRP rs1130864 [ 25 ] in the independent cohort of Moscow patients including individuals with the age at onset of more than 70 years (p f ≤0.05).…”
Section: Discussionmentioning
confidence: 99%
“…This is compelling evidence of validity of these associations, at least for the Russian population. It should be mentioned that earlier we described MI-associated genetic variants TGFB1 rs1982073 [ 24 ] and CRP rs1130864 [ 25 ] in the independent cohort of Moscow patients including individuals with the age at onset of more than 70 years (p f ≤0.05).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they showed -913G/C polymorphism was related to the increased levels of TGF-β1 gene and protein in MI patients [17]. Barsova et al [15] from Russia also explored the association between this SNP and MI risk in a population with 406 cases and 198 controls. They replicated the positive findings of the Iranian study [17], and showed -913G/C polymorphism was a risk factor for MI patients [15].…”
Section: Discussionmentioning
confidence: 99%
“…Barsova et al [15] from Russia also explored the association between this SNP and MI risk in a population with 406 cases and 198 controls. They replicated the positive findings of the Iranian study [17], and showed -913G/C polymorphism was a risk factor for MI patients [15]. However, Chen et al [23] from England revealed that TGF-β1 -913G/C polymorphism was not the risk of ischemic heart disease and MI in patients with rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations